What's in a word? Clarifying terminology on suicide-related communication. Issue 12 (1st December 2020) - Frey, Laura M.; Fulginiti, Anthony; Sheehan, Lindsay; Oexle, Nathalie; Stage, Dese'Rae L.; Stohlmann-Rainey, Jess
Abstract: Efforts to clarify suicide terminology fail to address nuances in suicide-related communication, often relying on poorly-defined terms or implying communication exists primarily as manipulation. In the present paper, we review examples from existing literature and explore how personal suicide-related communication differs from prevention and exposure communication. We also separate definitions for five common types of personal-suicide-related communication: (a) suicide-related disclosure, (b) suicide-related notification, (c) unintended suicide-related communication, (d) coerced suicide-related communication, and (e) conditional suicide-related communication. Finally, we provide specific ways in which standardized definitions can enhance both research and clinical efforts in the future.